Biomechanical characteristics of takeoff preparation and takeoff motion in different jumping types of elite male long jumpers - Shimizu, Y.; Ae, M.; Koyama, H. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This study investigated the biomechanical characteristics of takeoff preparation and takeoff motion for different types of elite male long jumpers. The subjects were 19 elite male long jumpers whose motion from the second to the last stride to takeoff was videotaped. The subjects were classified into two horizontal type (H-type) and vertical type (V-type) jumpers, based on the mean takeoff angle. The results are summarized as follows. (1) H-type jumpers tended to keep the trunk leaning forward and to retain their horizontal center of gravity (CG) velocity during takeoff preparation and takeoff phases. (2) V-type jumpers tended to extend the knee joint of the takeoff leg significantly at the touchdown of the takeoff phase and to obtain large vertical CG velocity by forward rotation of the body during the first half of the takeoff phase.